Cleaner power generation: an in-depth review of life cycle assessment for solid oxide fuel cells - Hilmi Hisyam Naimin,; Hawa Hishamuddin,; Ruhanita Maelah,; Muhammed Ali Shaikh Abdul Kader Abdul Hameed,; Amizawati Mohd Amir, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Nowadays, there is a growing emphasis on creating alternative power generation methods to replace outdated technologies like coal-fired power and hydroelectric plants. One promising solution is the Solid Oxide Fuel Cell (SOFC), which offers high energy efficiency, low carbon emissions, and cost-effectiveness. This study presents a focused examination of the Life Cycle Assessment (LCA) of SOFCs, with the objective of reducing dependence on non-renewable energy sources. The review encompasses a review of published articles between years 2016 to 2023 and an analysis of research gaps in SOFCs’ environmental performance. A systematic literature review underpins this investigation, where several publication selection criteria were considered including plants that can produce hydrocarbon such as biogas and biomass, utilization of LCA software as a method of assessment and incorporation of the life cycle impact assessment in the articles. The results suggest that using SOFC powered by biogas as a stationary power generator is a viable option. This is supported by recent LCA studies demonstrating that SOFCs using biogas have a reduced impact on climate change compared to other fuels. Implementing SOFCs holds great potential for a cleaner energy future, aligning with society’s goals for sustainable power production. For a more precise comparison of results, future LCA studies should adopt a multi-criteria environmental impact analysis using a consistent functional unit across different SOFC operations.